Improving issue representation with candidate-level voting advice applications - Germann, Micha; Mendez, Fernando; Wheatley, Jonathan; Djouvas, Constantinos; Nezi, Roula; Wall, Matthew (My University, 2025)
Voting advice applications (VAAs) have proliferated in recent years. However, most VAAs only match their users with parties, at least in part because creating a VAA matching voters to individual candidates tends to be more labour-intensive. This could be an important missed opportunity. Candidates may deviate from the party line, but voters are often unaware of the policy platforms of individual candidates and therefore rarely hold them accountable for their issue positions in candidate-based elections. VAAs providing information on issue congruence with individual candidates could help to rectify this. We evaluate the potential of candidate-level VAAs by integrating a randomized experiment into a real-world VAA whereby users were exposed either to candidate-level VAA advice or to more standard party-level VAA advice. Our results suggest that candidate-level VAAs are worth the extra effort: they help voters distinguish candidates from parties and cast votes that are more in line with their policy preferences.
Keywords: candidate preferences; democratic representation; field experiment; issue voting; voting advice applications